Evaluation of population genetic structure in two British Bos taurus breeds across five U.S. climate zones - Krehbiel, Bethany Cornwell, author; Thomas, Milton G., advisor; Blackburn, Harvey D., committee member; Enns, R. Mark, committee member; Speidel, Scott, committee member; Byrne, Patrick, committee member (Colorado State University. Libraries, 2017)
The objective of this thesis was to determine the fine-scale genetic diversity in Hereford and Red Angus cattle in relation to climate. Two hundred and twenty-five Hereford cattle and 174 Red Angus prominent AI sires were assigned to five U.S. climate regions (Cool Arid, Cool Humid, Transition Zone, Warm Arid, and Warm Humid). SNP-based methods were used to evaluate genetic diversity in the cattle in each of the U.S. climate zones. The first method utilized neutral SNP and the ADMIXTURE software to determine the genetic structure of the population. The second method used 66 SNP associated with traits potentially influenced by climate (body weight, heat stress, milk yield, heifer conception rate, and early embryonic survival) to determine Hardy-Weinberg Equilibrium and detection of loci under selection in each climate zone for Hereford and Red Angus breeds. Using 14,312 SNP, analyses of Hereford cattle revealed genetic structure that corresponded with climate zone. Additionally, 15 of the 66 SNP violated Hardy-Weinberg Equilibrium and detection of loci under selection (P < 0.05). Analysis of the 15 SNP revealed allele frequencies that were unique to the climate zones. Using 13,960 SNP, the genetic structure analysis of Red Angus sires revealed that there were eight sub-populations present within the breed. Additionally, 23 of the 66 SNP violated Hardy-Weinberg Equilibrium and detection of loci under selection (P < 0.05). Allele frequency analysis of the 23 SNP did not show genetic substructure that corresponded to climate zone. In conclusion, fine-scale evaluation of Hereford cattle revealed a genetic substructure corresponded with climate zone. However, fine-scale genetic substructure was detected in Red Angus sires, but did not correspond to U.S. climate zones. By identifying the genetic diversity in these prominent British beef breeds in relation to climate, management strategies can be formed to utilize the genetic diversity of these breeds to combat climate change.
Keywords: genetic diversity; molecular markers; SNP; Hereford; Red Angus; Bos taurus